New Working Methods of Cultural Centers - Rustamov Muhammad (Research Parks Publishing LLC, 2024)
the article talks about the requirements for the management of cultural centers, the reforms implemented in the field. To provide a complete understanding of the methods of systematic organization of creative processes of cultural centers, management of the activity of clubs.